Adoption Behavior of E-Money Usage - Miliani, Lani; ., Mia Tantri Diah Indriani (Information Management and Business Review, 2013)
Utilization of e-money as efficient and convenience payment method in Indonesia has been introduced since 2007. The growth of e-money card usage increased up to 53% in 2012, but the individual adoption is still low compared to total population of Indonesia. The objective of this study is to examine factors affecting customer adoption behavior of e-money and to examine the difference in intention to use/reuse e-money between adopter and non-adopter. The in-depth interview showed that risk and security were not the main consideration for using e-money; this result contradicts with the result of similar previous research in e-payment. Meaning, that in Indonesia consumers were not afraid of losing money while using emoney for transaction. The questionnaire based on the modification of Technology Adoption Model and indepth interview results. Sample of 143 respondents were taken to test the hypotheses, and analyzed using multivariate analysis methods. The results of the study-enhanced understanding of adoption behavior of emoney by describing perceived benefit as factor that influence intention to use/reuse e-money in Indonesia. This study also contributed in managerial practice that there are differences intention to use/reuse e-money between adopters and non-adopters due to lack of information of the products.